2019
DOI: 10.1021/acschembio.9b00619
|View full text |Cite
|
Sign up to set email alerts
|

Processivity in Bacterial Glycosyltransferases

Abstract: Extracellular polysaccharides and glycoproteins of pathogenic bacteria assist in adherence, autoaggregation, biofilm formation, and host immune system evasion. As a result, considerable research in the field of glycobiology is dedicated to study the composition and function of glycans associated with virulence, as well as the enzymes involved in their biosynthesis with the aim to identify novel antibiotic targets. Especially, insights into the enzyme mechanism, substrate binding, and transition-state structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 111 publications
4
49
0
Order By: Relevance
“…Previous studies demonstrated that the truncation of the TPR domain changed the oligomerization state of Cps1B from dimeric to monomeric (17). Oligomerization was described as structural basis for the processivity of various classes of enzymes (16,17). In contrast, extended polymer binding sites were shown to mediate processivity in carbohydrate polymerases (14)(15)(16)34).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies demonstrated that the truncation of the TPR domain changed the oligomerization state of Cps1B from dimeric to monomeric (17). Oligomerization was described as structural basis for the processivity of various classes of enzymes (16,17). In contrast, extended polymer binding sites were shown to mediate processivity in carbohydrate polymerases (14)(15)(16)34).…”
Section: Discussionmentioning
confidence: 99%
“…Oligomerization was described as structural basis for the processivity of various classes of enzymes (16,17). In contrast, extended polymer binding sites were shown to mediate processivity in carbohydrate polymerases (14)(15)(16)34). Although this study was focused on the biotechnological use of Cps1B, we performed initial limited proteolysis and surface plasmon resonance experiments to clarify if the TPR domain is involved in the binding of non-O-acetylated App1 polymer (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzymatic synthesis of cellulose in vitro is challenging because the natural biosynthetic machinery consists of complex membrane-embedded multi component systems 26 , that are hard to express in functional form. Furthermore, biosynthesis is processive and is biased towards production of very long oligomers 27,28 . Recent advances in employing biocatalysts for in vitro cellulose synthesis include production of high molecular weight (DP >200) cellulose or cellulose microfibrils from uridine diphosphate glucose (UDP-Glc) via exploitation of bacterial or plant-derived cellulose synthase (complexes) that are functionally reconstituted in lipid bilayers 29,30 .…”
Section: Introductionmentioning
confidence: 99%